CONCENTRATION AND FLUX OF ATMOSPHERIC SURFACTANTS FROM COASTAL WATERS - Latif, Mohd Talib; Mohamad, Che Abdul Rahim; Ali, Masni Mohd; Othman, Mohamed Rozali; Ramli, Nor Izanin; Hanif, Norfazrin Mohd (Marine Research in Indonesia, 2008)
This study tries to determine the concentration of sea surface microlayer from different coastal environments (Port Dickson, Negeri Sembilan and Perhentian Island, Terengganu). The concentration of surfactants in both sea surface microlayer and atmospheric aerosols were analysed by using colorimetric method as methylene blue active substances (MBAS) and diethyl violet active substances (DBAS). The results indicated that the concentration of surfactants as MBAS (0.421 +/- 0.040 imol l-1) and DBAS (0.294 +/- 0. 123 imol l-1) were still at the natural concentration level. The flux of surfactants from sea surface microlayer is expected around 2.3 Mmol yr-1 compared to the amount of 1300 Mmol yr-1 surfactants in atmospheric aerosols around marine ecosystem.